New K–12 Science Education Standards May Face Implementation Challenges. (30th April 2013) - Kumar, Mohi
Abstract : Kindergarten is not just a place to learn letters and numbers, practice finger painting, and listen to story time. If a new set of national science standards is adopted, it will also be the start of a carefully planned effort to engage students in science‐based activities throughout their K–12 academic careers.